The Workplace Support for Health Scale: Reliability and Validity of a Brief Scale to Measure Employee Perceptions of Wellness. Issue 2 (February 2021) - Kava, Christine M.; Passey, Debbie; Harris, Jeffrey R.; Chan, Kwun C. Gary; Hannon, Peggy A.
Purpose: To examine the reliability and validity of a brief measure (the Workplace Support for Health [WSH] scale) to assess employees' perceived support for a healthy lifestyle. Design: Repeated cross-sectional surveys. Setting: We collected employer- and employee-level survey data from small, low-wage workplaces in King County, WA enrolled in a randomized controlled trial. Sample: We analyzed data from 68 workplaces that had 2, 820 and 2, 640 employees complete surveys at baseline and 15 months, respectively. Measures: The WSH scale consisted of five items. To assess validity, we examined associations between the WSH scale and employer implementation of evidence-based interventions for health promotion, employee self-rated health, and job satisfaction. Analysis: We performed an exploratory factor analysis to assess the unidimensionality of the WSH scale items, and produced Cronbach's alpha coefficients to examine scale reliability. We ran regression models using generalized estimating equations to examine validity. Results: The factor analysis indicated one factor, which accounted for 59% of the total variance in the workplace support for health items. The scale had good reliability at baseline (α = 0.82) and 15 months (α = 0.83). Employer evidence-based intervention implementation was positively associated with WSH. WSH was also associated with higher self-rated health and job satisfaction. These associations indicate good concurrent validity. Conclusion: The WSH scale is a reliable and valid measure of perceived workplace support for health. Employers can use the scale to identify gaps in support and create a plan for improvement.